Análises citogenéticas em populações de Characidium (Pisces, Characidiinae) coletados em afluentes da bacia do Rio Grande, MG - Silva, Alexandre Rodrigues da (2005)
Cytogenetic studies were performed on four populations of the fishes belonging to the Characidium genus collected on small tributaries of the Grande River basin south of the State of Minas Gerais Brazil The studies brought forth two manuscripts whose abstracts are presented below Manuscript one Cytogenetic divergences between two sympatric species of Characidium (Teleostei Characiformes, Crenuchidae) from Machado River MG Brazil Cytogenetic studies were performed on two sympatric species of Characidium C gomesi and C cf zebra from the Grande river basin Minas Gerais State Brazil Although both species had a chromosome number equal to 50 chromosomes with a karyotype exclusively consisting of meta- and submetacentric chromosomes an interspecific diversity was detected concerning the size of the two first chromosome pairs of the karyotypes Active NORs were located at terminal position on the long arm of the 17th pair in C gomesi and at subterminal position on the long arm of the 23th pair in C cf zebra The fluorochrome CMA3 stained only the NOR-bearing pair of chromosomes of both species The pattern of heterochromatin also showed some differentiation among these species being restricted to centromeric or pericentromeric region in C cf zebra and practically absent in C gomesi These data are discussed concerning chromosome diversification in this fish group Manuscript two Karyotype characterization of two alopatric populations of Characidium cf zebra (Pisces Crenuchidae) from Grande River basin MG Brazil Two populations of Characidium cf zebra were collected in tributaries from Grande river basin and analyzed from the cytogenetic viewpoint Both C cf zebra populations studied had the same karyotypic structure with diploid number 2n igual 50 metacentric/submetacentric chromosomes and fundamental number 100 C-band patterns showed heterochromatin only in the centromeric region Results of analyses from the nucleolus organizer region obtained by silver nitrate staining was observed on one pair of small submetacentric chromosomes at the terminal position of the long arm Treatment with chromomycin A3 (CMA3) showed regions rich in GC base pairs in the NOR-bearing pair of chromosomes on both populations and in one metacentric chromosome with bright signal on the terminal position in the long arm in the Coqueiro stream population Some aspects related to C cf zebra chromosome composition are discussed